Perkembangan Kognitif Anak Usia 5 Tahun Dalam Mengklasifikasikan Benda Menggunakan Asemen Skala Penilaian - Sitanggang, Fitri Romasi; Munthe, Indah Pefrianti Dali; Sinaga, Gloria Stevany A; Purba, Gloria Verintina; Buulolo, Sefrin Hewi (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to determine the extent of cognitive development of 5-year-old children in the ability to classify natural objects based on their characteristics and places. This study uses a quantitative approach with a descriptive method, involving 6 children from two Kindergartens in Medan City. The instrument used is a cognitive development assessment scale developed based on the PAUD Curriculum, covering aspects of recognizing natural objects, grouping them, and mentioning their benefits. Data collection techniques are carried out through observation, interviews, and documentation. The results of the study showed that 80% of children were in the Very Well Developed (BSB) category, while 20% of children were still in the Still Developing (MB) category. This study emphasizes the importance of assessment to identify children's abilities and needs and as a basis for designing appropriate learning that is in accordance with the cognitive development of early childhood.